2009
DOI: 10.1155/2009/969764
|View full text |Cite
|
Sign up to set email alerts
|

Child Skeletal Fluorosis from Indoor Burning of Coal in Southwestern China

Abstract: Objectives. We assess the prevalence and pathogenic stage of skeletal fluorosis among children and adolescents residing in a severe coal-burning endemic fluorosis area of southwest China. Methods. We used a cross-sectional design. A total of 1,616 students aged between 7 and 16 years in Zhijin County, Guizhou, China in late 2004 were selected via a cluster sampling of all 9-year compulsory education schools to complete the study questionnaire. Any student lived in a household that burned coal, used an open-bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…High concentrations of fluoride can also produce long-term bone damage in children and adults such as skeletal fluorosis. [1] Even intelligence quotient (IQ) has been associated with fluoride exposure. [2]…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of fluoride can also produce long-term bone damage in children and adults such as skeletal fluorosis. [1] Even intelligence quotient (IQ) has been associated with fluoride exposure. [2]…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported fluoride contents of roasted chili, corn, squash, potatoes and cured meat reached 419.8 mg/kg (33), 39.5 mg/kg (33), 121.8 mg/kg (34), 134.6 mg/kg (35), and 182.2 mg/kg (36), respectively. Corn and potatoes are the primary foods consumed by residents of Zhijin and daily mean fluoride intake (per person) from corn was 37.6 and 3.5 mg from potatoes (37). Previous studies demonstrated that particular roasted foods, such as corn, chilli, and potatoes, were the primary pathological cause of coal-burning fluorosis, because of the fluorine pollution coming from the coal briquettes and binder clay (6,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Corn and potatoes are the primary foods consumed by residents of Zhijin and daily mean fluoride intake (per person) from corn was 37.6 and 3.5 mg from potatoes (37). Previous studies demonstrated that particular roasted foods, such as corn, chilli, and potatoes, were the primary pathological cause of coal-burning fluorosis, because of the fluorine pollution coming from the coal briquettes and binder clay (6,37,38). Therefore, the present study suggests that the easy-to-roast dietary pattern in our study was positively associated with a risk of fluorosis not because the foods themselves were a source of fluorine, but rather roasting food over coal stoves caused the fluorine pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of fluorosis were caused by drinking fluorous water. In China, fluorosis is caused by drinking water as well as inhaling combustion fumes of coal being used as an indoor fuel source [28][29][30][31]. Guizhou is one of the most severely afflicted areas of endemic fluorosis in China and this occurrence is due to indoor coal burning [30].…”
Section: Introductionmentioning
confidence: 99%